(untitled) (Acta Scientiarum. Biological Sciences, 2009)
In order to analyze the structure and dynamics of the periphytic community in Iraí reservoir, an eutrophic environment, samples were taken in two seasons: summer (April) and winter (September) of 2002, in littoral areas from three regions of the reservoir (upper, intermediary and lower). Rooted aquatic vegetation were used as sampling substrates, because they were found in all sampling sites. A total of 297 species was recorded (225 in April, 73 exclusive taxa; and 224 in September, with 72 exclusive taxa). Bacillariophyceae predominated in all regions in both seasons, in species number, as well in density. There were differences in richness among zones; intermediary and lower regions were more similar, mainly in September. The periphytic algae density differed significantly between seasons (p = 0.002; F = 16.48), with lower values in the summer. No significant difference in density was recorded among zones.